1983
DOI: 10.1002/jez.1402280316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an hemipteran juvenile hormone: In vitro biosynthesis of JH III by Dysdercus fasciatus

Abstract: Corpora allata of the African cotton stainer, Dysdercus fasciatus Sign. (Hemiptera: Pyrrhocoridae), produce radiolabeled methyl-l0,ll-epoxy-3,7,11-trimethyldodeca-2E,6E-dienoate (JH 111) when cultured in a medium containing L-[meth~l-'~C] methionine. Similar in vitro studies show JH TI1 biosynthesis by cultured corpora allata of Lygaeid and Pentatomid species. This is the first identification of a juvenile hormone in Hemiptera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In diapausing adults of P. apterus, the activity of CA was inhibited by the brain via nervous connections [23,24]. The production of methyl farnesoate [25] and JH III [26] by the CA in vitro was reported in Dysdercus fasciatus, O. fasciatus, and Nezara viridula.…”
Section: Heteropteran Insects In Jh Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…In diapausing adults of P. apterus, the activity of CA was inhibited by the brain via nervous connections [23,24]. The production of methyl farnesoate [25] and JH III [26] by the CA in vitro was reported in Dysdercus fasciatus, O. fasciatus, and Nezara viridula.…”
Section: Heteropteran Insects In Jh Researchmentioning
confidence: 96%
“…Thus far, at least 7 species from 4 families of Heteroptera seem to share this product [7,9,10,30]. Although the CA of O. fasciatus, D. fasciatus, and N. viridula were reported to produce JH III and/or methyl farnesoate in vitro [25,26] and JH I was found in the hemolymph of R. pedestris (formerly R. clavatus) [31], the production of JH III and JH I in N. viridula and R. pedestris, respectively, was not confirmed [9].…”
Section: Evidence For a New Jh In Stink Bugsmentioning
confidence: 99%
“…Feldlaufer et al (1982) examined the products released by the CA of Dysdercus fasciatus in vitro and concluded that the product was methyl farnesoate, a precursor of JH III. Using a different medium for the in vitro incubation, Bowers et al (1983) found that the CA of D. fasciatus, Oncopeltus fasciatus, and Nezara viridula also released JH III. However, our laboratory has found that JH III does not affect the follicle cells of R. prolixus in vitro and that JH III will not compete for the binding site for JH I on the follicle cell membrane (Ilenchuk and Davey, 1987).…”
Section: The Identity Of Heteropteran Jhmentioning
confidence: 98%
“…A better understanding of their JHs will enable more effective management. However, the JHs of heteropteran species have long been greatly controversial (Baker et al, 1988;Bowers et al, 1983;Kotaki, 1993;Teal et al, 2014). Kotaki et al (2009Kotaki et al ( , 2011 reported a novel JH, methyl (2R,3S,10R)-2,3;10,11bisepoxyfarnesoate, commonly named juvenile hormone III skipped bisepoxide (JHSB3) (Fig.…”
Section: Introductionmentioning
confidence: 99%